A mental architecture modeling of inference of sensory stimuli to the teaching of the deaf - Guimaraes, Rubens Santos (Faculdade de Ciências e Letras/Unesp, 2016)
The transmission and retention of knowledge rests on the cognitive faculty of the concepts linked to it. The repeatability of your applications builds a solid foundation for Education, according to cultural and behavioral standards set by the Society. This cognitive ability to infer on what we observe and perceive, regarded as intrinsic human beings, independent of their physical capacity. This article presents a conceptual model Mental Architecture Digitized – AMD, enabling reproduce inferences about sensory stimuli deaf, focused on the implementation of a web system that aims to improve the teaching and learning of students with hearing disability. In this proposal, we evaluate the contextual aspects experienced by learners during the interactions between the constituent elements of a study session, based on experiments with two deaf students enrolled in regular high school. The results allow us to infer the potential of a computer communications environment to expand the possibilities of social inclusion of these students.